Analysis of Motivation, Work Discipline, and Skills on Employee Performance at the Medan Agricultural Development Polytechnic - M. Satya Adifka; Ikhah Malikhah; Ahmad Aswan Waruwu (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of motivation, work discipline, and skills on employee performance at the Medan Agricultural Development Polytechnic. The research method used is a quantitative approach with a correlational study design. The population in this study consisted of 111 employees, with a sample of 53 respondents determined using the Slovin formula. Data collection was conducted through the distribution of questionnaires, while data analysis utilized multiple linear regression with the assistance of SPSS 25. The results indicate that, partially, motivation has a positive and significant effect on employee performance with a t-value of 3.572 and a significance level of 0.001 < 0.05. Work discipline also has a positive and significant effect on employee performance, with a t-value of 4.147 and a significance level of 0.000 < 0.05. Skills have a positive and significant effect on employee performance, with a t-value of 6.802 and a significance level of 0.000 < 0.05, and are the most dominant variable. Simultaneously, motivation, work discipline, and skills have a positive and significant effect on employee performance, with an F-calculated value of 26.646 and a significance level of 0.000 < 0.05. The adjusted R-squared value of 0.597 indicates that 59.7% of the variation in employee performance can be explained by these three variables, while the remainder is influenced by other factors outside the scope of this study. Thus, continuous improvement in motivation, work discipline, and skills is essential to enhance employee performance at the Medan Agricultural Development Polytechnic.